Students' online argumentative peer feedback, essay writing, and content learning: does gender matter?. Issue 6 (17th August 2020) - Noroozi, Omid; Hatami, Javad; Bayat, Arash; van Ginkel, Stan; Biemans, Harm J. A.; Mulder, Martin
ABSTRACT: Whilst the importance of online peer feedback and writing argumentative essays for students in higher education is unquestionable, there is a need for further research into whether and the extent to which female and male students differ with regard to their argumentative feedback, essay writing, and content learning in online settings. The current study used a pre-test, post-test design to explore the extent to which female and male students differ regarding their argumentative feedback quality, essay writing and content learning in an online environment. Participants were 201 BSc biotechnology students who wrote an argumentative essay, engaged in argumentative peer feedback with learning partners in the form of triads and finally revised their original argumentative essay. The findings revealed differences between females and males in terms of the quality of their argumentative feedback. Female students provided higher-quality argumentative feedback than male students. Although all students improved their argumentative essay quality and also knowledge content from pre-test to post-test, these improvements were not significantly different between females and males. Explanations for these findings and recommendations are provided.